Influence of occupational stress on psychological well-being of teachers in Ayacucho - Berrocal Aréstegui, Frank Isaac (2023)
The research conducted sought to determine the way in which work stress influences the psychological well-being of teachers, using a methodology anchored in the positivist paradigm, quantitative approach, basic type, explanatory level and non-experimental, transectional, correlational-causal and field design. The study sample consisted of 81 teachers out of a total of 136 from three educational institutions and a classroom of students in a doctoral program, who were selected by non-probabilistic convenience sampling. Psychometrics was used as a data collection technique and psychological tests were used to measure the variables, namely Ivancevich and Matteson's (1989) Work Stress Scale and Casullo's (2002) Psychological Well-Being Scale, adapted and validated respectively in the Peruvian context. The findings revealed that job stress significantly and negatively influences teachers' psychological well-being, being responsible for 39.9% of its variability, which confirmed the research hypothesis. In addition, a prevalence of high and medium levels of work stress was identified in 44.4% of those evaluated, and a low level of psychological well-being in 79.0% of them.